2019
DOI: 10.1002/mc.23134
|View full text |Cite
|
Sign up to set email alerts
|

FSIP1 is correlated with estrogen receptor status and poor prognosis

Abstract: Fibrous sheath interacting protein 1 (FSIP1) is frequently activated in a variety of tumors including breast cancer. However, the clinical significance of FSIP1 in hormone receptor (HR)-positive breast cancer is unclear. We analyzed the expression and clinical significance of FSIP1 in human breast cancer databases. A comprehensive analysis of 1094 gene expression profiles of breast cancer in The Cancer Genome Atlas revealed that FSIP1 overexpression correlated with decreased overall survival in HR-positive bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…1A ). Among the 7 genes, GATA3 , FSIP , and FOXA1 have been suggested to associate with chemoresistance in ER-positive breast cancers 16 , 22 . Notably, in both Cancer Genomic Atlas (TCGA) and CCLE databases, the meiotic gene SYCP2 is commonly upregulated in breast, cervical, and ovarian cancers and also detected in other cancer types, including lung, head-and-neck, and bladder cancers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A ). Among the 7 genes, GATA3 , FSIP , and FOXA1 have been suggested to associate with chemoresistance in ER-positive breast cancers 16 , 22 . Notably, in both Cancer Genomic Atlas (TCGA) and CCLE databases, the meiotic gene SYCP2 is commonly upregulated in breast, cervical, and ovarian cancers and also detected in other cancer types, including lung, head-and-neck, and bladder cancers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of tumor biology, FSIP1 is currently recognized as a cancer antigen which is highly expressed in breast, colon, lung, and bladder cancers and associated with poor prognosis. In breast cancer tissues, it has been found that FSIP1 expression is correlated with HER2 positive and Ki67 expression, and it is associated with poorer postoperative disease-specific survival probability [22]. Studies confirmed that FSIP1 directly binded to HER2 and inhibited the expression of multiple growth factors in HER2positive breast cancer cells, leading to a decrease in cell proliferation, cell migration, and invasion capabilities and an increase in apoptosis.…”
Section: Disease Markersmentioning
confidence: 93%
“…Five days later, medium-Matrigel-cells were centrifuged, and cell pellets were embedded in histogel (Thermo Scientific; Cat#HG-4000-012). The mixture was fixed in 4% paraformaldehyde overnight followed by dehydration, paraffin embedding, sectioning, and immunohistochemistry was performed as previously described [9] . Rabbit anti-HER2 (1: 500) antibody was purchased from Abcam (ab134182).…”
Section: Methodsmentioning
confidence: 99%